2016
DOI: 10.3892/mmr.2016.5555
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasoconstriction reactions and plasma levels of ETBR, ET-1, and eNOS in patients with chronic high altitude disease

Abstract: The aim of the present study was to examine cerebral vasoconstriction in patients with chronic high altitude disease [cerebrovascular reactivity (CVR)], and to evaluate differences in alterations of brain vascular contractile reactivity of chronic mountain sickness (CMS) patients and healthy controls. Alterations of endothelin (ET) and its receptor, as well as endothelial nitric oxide synthase (eNOS) levels in the plasma were examined to determine the cerebral reservation capacities in CMS patients. Transcrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Given that EDNRB was first identified in human HA dwellers from Ethiopia known to be best adapted to HA [32], it is interesting to note a recent study showing that the level of EDNRB in serum was significantly higher in chronic mountain sickness (CMS) patients [33]. Furthermore, the cerebrovascular reactivity (CRV), i.e., the change in cerebral blood flow in response to a stimulus, was reportedly lower in these patients pretty much similar to patients with cardiac failure [34].…”
Section: Discussionmentioning
confidence: 99%
“…Given that EDNRB was first identified in human HA dwellers from Ethiopia known to be best adapted to HA [32], it is interesting to note a recent study showing that the level of EDNRB in serum was significantly higher in chronic mountain sickness (CMS) patients [33]. Furthermore, the cerebrovascular reactivity (CRV), i.e., the change in cerebral blood flow in response to a stimulus, was reportedly lower in these patients pretty much similar to patients with cardiac failure [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that our examined groups with type 2 DM and without DM as well as those with D and without D did not demonstrate differences in the examined clinical and demographic parameters, which could also have affected the lack of difference in the circulating eNOS levels. Many studies have revealed that patients on HD have many specific factors that impede eNOS activity, such as eNOS gene polymorphism [ 29 ], hyperparathyroidism [ 30 ], and oxidative stress [ 31 ]. The aforementioned uraemic eNOS inhibitors can dim and obliterate the effects of diabetes mellitus and dyslipidaemia on eNOS activity in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of acute hypobaric hypoxia, the body can ensure a supply of oxygen and energy to the brain by strengthening ventilation, accelerating the heart rate, increasing blood pressure, and changing the arterial blood gas balance. Acute hypoxia and hypoxia can stimulate the nervous and endocrine systems and may lead to the release of cytokines, such as endothelium-derived nitric oxide (NO), that cause systemic vasoconstriction, thereby increasing the CBF rate ( Wu et al, 2016 ). With gradual adaptation of the body to a high altitude environment, cerebrovascular reactivity, and vasomotor function are gradually restored and CBF slowly decreases to a level close to the normal range ( Lucas et al, 2011 ; Ainslie and Subudhi, 2014 ).…”
Section: Discussionmentioning
confidence: 99%